Influenza A (H1N1)-associated severe complications; hemolytic uremic syndrome, myocarditis, acute necrotizing encephalopathy - KEPENEKLİ KADAYİFCİ, EDA; ÖZTÜRK, MAKBULE NİLÜFER; YAKUT, NURHAYAT (J INFECTION DEVELOPING COUNTRIES, 2019)
Influenza is a generally self-limited infection agent that only rarely causes severe complications. To increase awareness about its serious complications, we report three cases of influenza A (H1N1) infection complicated with hemolytic uremic syndrome, myocarditis and acute necrotizing encephalopathy. In all three cases, nasopharyngeal samples confirmed influenza A (HIN1) infection by antigen test and multiplex PCR detection. The first case, a 3-year-old girl, had respiratory distress, anemia, thrombocytopenia and renal failure at admission, and was diagnosed with hemolytic uremic syndrome. Supportive treatment and oseltamivir did not prevent the development of chronic renal failure. The second case, a 5-year-old girl admitted with lethargia and flu-like symtoms and was diagnosed with myocarditis and cardiogenic shock. Oseltamivir and supportive treatment including extra-corporeal membrane oxygenation (ECMO) failed. She died on the 3rd day of admission. The third case, a 21-month-old boy, presented with decreased level of consciousness and was diagnosed with acute necrotizing encephalopathy with the aid of cranial magnetic resonance imagining (MRI). He was discharged without any neurological sequelae three weeks after admission. It should be kept in mind that influenza virus does not always cause a self-limited flu. Multidisciplinary management, early diagnosis and antiviral treatment are critical for the disease and to prevent its life-threatening complications.
Keywords: influenza; H1N1; complications; encephalopathy; HUS; myocarditis; VIRUS; CHILDREN; CHEMOPROPHYLAXIS; ENCEPHALITIS; INFECTION; DIAGNOSIS; H1N1; PCR